2022
DOI: 10.1101/2022.11.22.517461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial defects leading to arrested spermatogenesis and ferroptosis in a mouse model of Leigh Syndrome

Abstract: Impaired spermatogenesis and male infertility are common manifestations of mitochondrial diseases, but the underlying mechanisms are unclear. Here we show that mice deficient for PARL, the mitochondrial rhomboid protease, a recently reported model of Leigh syndrome, develop postpubertal testicular atrophy caused by arrested spermatogenesis and germ cell death independently of neurodegeneration. Genetic modifications of PINK1, PGAM5, and TTC19, three major substrates of PARL with important roles in mitochondria… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
0
0
Order By: Relevance
“…The mitochondrial energetic metabolism and ferroptosis closely interact with each other 58 . However, there are still some controversies concerning the role of energetic metabolism in ferroptotic process [59][60][61][62] . In this study, we demonstrated that SOX13 boosts NADPH production by upregulating SCAF1 to drive ferroptosisresistance.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial energetic metabolism and ferroptosis closely interact with each other 58 . However, there are still some controversies concerning the role of energetic metabolism in ferroptotic process [59][60][61][62] . In this study, we demonstrated that SOX13 boosts NADPH production by upregulating SCAF1 to drive ferroptosisresistance.…”
Section: Discussionmentioning
confidence: 99%